Geochemistry characteristics of rare earth elements in the permo-carboniferous Taiyuan Formation coal in Ordos Basin—Taking Ningdong coalfield as an example - Fenghua MA; Donggang WANG; Qingzhi HE; Ruiyun MA; Cheng WANG; Xiaobing YANG (Meitan kexue jishu)
The study of the geochemical characteristics of rare earth elements (REE) in coal has important indicative significance in terms of sedimentary environment and material source in coal basin. In order to further explore the geochemical characteristics of systematic elements in Carboniferous-Permian coal in the Ordos Basin, taking the Permo-Carboniferous Taiyuan Formation (Fm) coal in Nindong coalfield as the research object to study the geochemistry characteristics of REE and discussed its occurrence characteristics and origin, base on the data from X-ray fluorescence spectrometer and plasma mass spectrometer. The result show that: The average content of REE in Permo-Carboniferous Taiyuan Fm coals from Nindong coalfield is 91.91 μg/g, which is lower than the average content of 135.89 μg/g in China coals. The obviously negative Eu abnormity, unobvious Ce abnormity, LaN/YbN, LaN/LuN, LaN/SmN, LREE/HREE and the REE distribution patterns normalized by the upper crust all reflect the characteristics of low fractionation of light and heavy REE and relative enrichment of heavy rare earth elements in coals. The REE in the coal inherit the characteristics of the rare earth elements in the source rock area, and in the sedimentary and coal-forming stages, under the combined action of temperature, pressure, pH value and redox conditions. The REE in coal mainly occurs in clay minerals, which can be verified by the positive correlation between rare earth elements and ash, Si, Al, Na, K. The diagrams of ∑Lei-La/Ibu, ∑-Li-δ/δ-Ou, and Σli-La/Lu indicate that the Carboniferous-Permian coal in the Ningdong coalfield was formed in the sedimentary setting of the Lower Delta Plain and the Lower Delta-Delta Plain, all of which were affected by seawater to varying degrees. The source, content and occurrence characteristics of REE in Permo-Carboniferous Taiyuan Fm coals from Ningdong coalfield are mainly controlled by the supply of felsic terrigenous clasts, but also affected by local micro-topography, micro-geomorphology and micro-environment, the impact of seawater and diagenesis are limited.